2015
DOI: 10.1128/aac.05152-14
|View full text |Cite
|
Sign up to set email alerts
|

Efflux as a Glutaraldehyde Resistance Mechanism in Pseudomonas fluorescens and Pseudomonas aeruginosa Biofilms

Abstract: A major challenge in microbial biofilm control is biocide resistance. Phenotypic adaptations and physical protective effects have been historically thought to be the primary mechanisms for glutaraldehyde resistance in bacterial biofilms. Recent studies indicate the presence of genetic mechanisms for glutaraldehyde resistance, but very little is known about the contributory genetic factors. Here, we demonstrate that efflux pumps contribute to glutaraldehyde resistance in Pseudomonas fluorescens and Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…In this study, the PA1874 -1877 operon was identified as a novel efflux system potentially involved in biofilm-specific resistance to antibiotics: the expression of PA1874 was found to be 10-fold higher in sessile than in planktonic cells, deletion of the operon only affected susceptibility to tobramycin in biofilms, and overexpression of the operon decreased the susceptibility toward selected aminoglycosides and fluoroquinolones in planktonic cells (27). In addition, in Pseudomonas fluorescens, expression of two efflux systems was up-regulated in glutaraldehydetreated biofilms, and efflux pump inhibitors increased sensitivity of P. aeruginosa and P. fluorescens biofilms to this disinfectant, confirming that not only antibiotic resistance is mediated by efflux (28). Finally, it was observed that planktonic P. aeruginosa cells grown under hypoxic conditions showed an increased expression of MexEF-OprN (29).…”
Section: Pseudomonas Aeruginosamentioning
confidence: 64%
“…In this study, the PA1874 -1877 operon was identified as a novel efflux system potentially involved in biofilm-specific resistance to antibiotics: the expression of PA1874 was found to be 10-fold higher in sessile than in planktonic cells, deletion of the operon only affected susceptibility to tobramycin in biofilms, and overexpression of the operon decreased the susceptibility toward selected aminoglycosides and fluoroquinolones in planktonic cells (27). In addition, in Pseudomonas fluorescens, expression of two efflux systems was up-regulated in glutaraldehydetreated biofilms, and efflux pump inhibitors increased sensitivity of P. aeruginosa and P. fluorescens biofilms to this disinfectant, confirming that not only antibiotic resistance is mediated by efflux (28). Finally, it was observed that planktonic P. aeruginosa cells grown under hypoxic conditions showed an increased expression of MexEF-OprN (29).…”
Section: Pseudomonas Aeruginosamentioning
confidence: 64%
“…This bacteria has an outer sheath-like structure that might provide physical characteristics that confers resistance to biocides (75). Resistance of some Pseudomonas species to glutaraldehyde has been related to the presence of genetic mechanisms, specifically, the expression of efflux pumps and induction of modulators of biofilm formation (76). Efflux pumps can be induced when microorganisms are under stress conditions which contributes to higher bacterial resistance of stressed populations to antimicrobial substances and could be the reason for the higher increase in the relative on October 11, 2020 by guest…”
Section: Downloaded Frommentioning
confidence: 99%
“…Age related resistance to glutaraldehyde, ahigh level disinfectant also used in endoscope disinfection, has been reported in P. aeruginosa and P. flourescens. (38) Resistance to disinfection may be due to the components of the ECM, which react with the disinfectant before the agent reaches the bacterial cell surface. If this is the case then higher biomass should result in reduced effectiveness of disinfection.…”
Section: Accepted Manuscriptmentioning
confidence: 99%